THE CHARACTERISTICS OF EXPORTERS AMONG HIGH-TECHNOLOGY MANUFACTURERS BASED IN WARSAW - Skala, Agnieszka; Rostek, Katarzyna (Acta Scientiarum Polonorum. Oeconomia, 2015)
The goal of presented study was to identify and describe the high-tech manufacturing sector (HT) in Warsaw and to indicate the part having the highest market potential. Based on the results of previously executed studies, the sub-sector of HT-exporters (HTME) was identified as the most promising group of companies in the high-technology sector. In the article, the description of this sub-sector is presented and its specifics are discussed. Their legal status is more frequently corporate, their size is larger (in terms of the number of employed), as well as the scope of their cooperation with regard to science and the self-assessment of innovativeness. The assumption that the exporters of high-technology products are elite among HT manufacturers has been confirmed.